The Predictive Power of Political Pundits: Prescient or Pitiful? - Phillip Metaxas; Andrew Leigh (Center for Economic Studies and ifo Institute (CESifo), 2013)
Although Australian political pundits frequently make predictions about the future, little systematic evidence exists on the accuracy of these predictions. To assess the predictive power of experts, we survey the transcripts of two well-known political programs - Insiders and Meet the Press - and record all falsifiable forecasts. Looking at the three months prior to both the 2007 and 2010 Federal elections, we are struck by the paucity of falsifiable predictions, with most pundits heavily qualifying their predictions (so that they can never be said to be wrong). In 32 hours of television, we identify 20 falsifiable forecasts in our sample, of which we judge 13 to be correct. We conclude with some suggestions for political talk shows and for political scientists seeking to better analyse expert predictions.
Keywords: D70; D80; 330; expert prediction; forecast accuracy; elections